2019
DOI: 10.1515/pp-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Staging laparoscopy and Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) for peritoneal metastasis: safe access to the abdomen

Abstract: BackgroundPressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) is an innovative drug delivery technique. Most common indication is palliative therapy of peritoneal metastasis of gastrointestinal and gynecological origin in the salvage situation. Access to the abdomen is the critical step of the procedure, since most patients had previous surgery. Potential pitfalls include non-access because of adhesions, bowel access lesions and postoperative subcutaneous toxic emphysema.MethodsWe propose a technique, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…26 For this reason, clinical teams continue to search for improved means of access to the peritoneal cavity to avoid complications and deterioration of therapeutic management. 27 In our study, intraoperative intravenous 5-FU/L combined with PIPAC-Ox did not increase the postoperative complication rate compared with PIPAC-Ox alone. Systemic chemotherapy using oxaliplatin and 5-FU/L has shown great success in the management of metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 39%
“…26 For this reason, clinical teams continue to search for improved means of access to the peritoneal cavity to avoid complications and deterioration of therapeutic management. 27 In our study, intraoperative intravenous 5-FU/L combined with PIPAC-Ox did not increase the postoperative complication rate compared with PIPAC-Ox alone. Systemic chemotherapy using oxaliplatin and 5-FU/L has shown great success in the management of metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 39%
“…Moreover, patients who are eligible for PIPAC treatment often have prior abdominal surgery as CRS or HIPEC. This may explain the observed failure rate which is higher due to attempts to access the abdomen to perform PIPAC [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] found that bowel injury related to a Veress needle or trocar insertion was the most common complication. For this reason, clinical teams continue to search for improved means of access to the peritoneal cavity to avoid complications and the deterioration of therapeutic management [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic examination, access to the abdomen is largely dependent on patient selection and surgical ability, and after cytoreductive surgery, peritonectomy, and HIPEC, it shows a non-access rate higher than after other procedures [ 17 ].…”
Section: Relative Contraindications To Pipac or Laparoscopic Approachmentioning
confidence: 99%